Case report: Neurofibromatosis type 1 gastrointestinal stromal tumor and small bowel adenocarcinoma with a novel germline NF1 frameshift mutation - Zhang, Wuming; Hu, Xianqin; Chen, Zhikang; Lai, Chen (Frontiers in Oncology, 2022)
A synchronous case of small bowel adenocarcinoma(SAB) is reported, accompanied with gastrointestinal stromal tumor（GIST）,and gangliocytomain in an elderly woman with neurofibromatosis type 1 (NF-1). A 67-year-old female was hospitalized with the chief complaint of abdominal pain, the computed tomography scan indicated a large bowel mass. Multiple tumors were found in the small intestine, through which two larger tumors (7 cm and 1.5 cm) were resected. A novel germline NF1 mutation and a PMS2 mutation were identified after genetic testing, followed by the exploration of possible relationship between them in promoting tumorigenesis. Our results suggest multiple gastrointestinal tumors emerging in NF1 patients, and genetic testing can better guide postoperative treatment in a more efficient way.